Applications of Artificial Intelligence in Dentomaxillofacial Diagnostics - Iván Claudio Suazo Galdames (Editorial Ciencias Médicas, 2024)
Introduction: The introduction of artificial intelligence-driven applications is revolutionizing dentomaxillofacial imaging. Objectives: To describe the current status of artificial intelligence applications in dentomaxillofacial diagnostics; to assess their impact; and to identify future directions for research and implementation. Methods: A narrative review was performed, using systematic searches in databases such as PubMed, Google Scholar, IEEE Xplore, among others; the study focused on articles published from 2010 to the present. Researches applying artificial intelligence technologies in dentomaxillofacial diagnosis were included; their quality and relevance were evaluated using the established tools. Results: Artificial intelligence, especially deep learning, has shown significant improvements in image segmentation, disease detection and treatment planning in dentomaxillofacial imaging. Artificial intelligence techniques have enabled automation of image analysis tasks, improved efficiency and diagnostic accuracy. Conclusions: Artificial intelligence has significant potential to revolutionize dentomaxillofacial imaging, as it offers improvements in diagnostic accuracy, efficiency in image interpretation, and treatment planning. Further research is needed to overcome technical, ethical and privacy challenges and to validate the clinical applicability of these technologies.